Assessing the Resources of Public Libraries for Their Conversion Towards Community Learning Centres - Javed Iqbal Rana,Rubina Bhatti (IJoLIS, 2024)
Purpose: This study aims to assess whether government public libraries in Punjab (PLsP) have enough resources and services to take up the role of Community Learning Centres (CLCs) to become proactive organs of the community for livelong learning.